The aging of a young nation: Population aging in Singapore - MALHOTRA, Rahul (Institutional Knowledge at Singapore Management University, 2019)
The juxtaposition of a young city-state showing relative maturity as a rapidly aging society suffuses the population aging narrative in Singapore and places the “little red dot” on the spotlight of international aging. We first describe population aging in Singapore, including the characteristic events that shaped this demographic transition. We then detail the health care and socioeconomic ramifications of the rapid and significant shift to an aging society, followed by an overview of the main aging research areas in Singapore, including selected population-based data sets and the main thrust of leading aging research centers/institutes. After presenting established aging policies and programs, we also discuss current and emerging policy issues surrounding population aging in Singapore. We aim to contribute to the international aging literature by describing Singapore’s position and extensive experience in managing the challenges and maximizing the potential of an aging population. We hope that similar graying populations in the region will find the material as a rich source of information and learning opportunities. Ultimately, we aspire to encourage transformative collaborations—locally, regionally, and internationally—and provide valuable insights for policy and practice.